THE RELATIONSHIP BETWEEN MOTIVATION AND ENGLISH ACHIEVEMENT OF STUDENTS OF HOTEL MANAGEMENT STUDY PROGRAM AT BRAWIJAYA UNIVERSITY - malik handika (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract : The study aims is to identify the relationship between motivation and English achievement of students of Hotel Management study program at Brawijaya University. The motivation itself consist of 12 aspects, those are interest in foreign language, motivational intensity, parental encouragement, English class anxiety, English teacher evaluation, attitudes toward learning English, attitudes towards English-speaking people, integrative orientation, desire to learn English, English course evaluation, English use anxiety and instrumental orientation which is correlated by achievement. These indicators of Motivation tried to be correlated with the basic score of English as achievement instrument. The research method used in this study is quantitative research procedures with multiple correlation design. It involves 31 students study program of Hotel Management at Brawijaya as the sample. To collect the data, the writer used AMTB questionnaire consisting of 104 items as the instrument of motivation and the basic score of English as an achievement instrument. Indeed, the result of this study is shown by the R-value is 0.647 converted to F value which has 1.079 while the significance value is 0.429. Since 0.429 is higher than 0.05, it can be stated that the alternative hypothesis is rejected. Therefore, the conclusion is that there is no relationship between motivation and English achievement of students of Hotel Management study program at Brawijaya University.Key Words: correlation, motivation, achievement